Parcel delivery - opportunities & challenges for Capital Logistics & C-Express Ltd. - Ornob, Md. Monzurul Huq. (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.